The Canadian Medical Student Ultrasound Curriculum: A Statement From the Canadian Ultrasound Consensus for Undergraduate Medical Education Group. (13th January 2020) - Ma, Irene W. Y.; Steinmetz, Peter; Weerdenburg, Kirstin; Woo, Michael Y.; Olszynski, Paul; Heslop, Claire L.; Miller, Stephen; Sheppard, Gillian; Daniels, Vijay; Desy, Janeve; Valois, Maxime; Devine, Luke; et al.
Abstract : Objectives: This study sought to establish by expert review a consensus‐based, focused ultrasound curriculum, consisting of a foundational set of focused ultrasound skills that all Canadian medical students would be expected to attain at the end of the medical school program. Methods: An expert panel of 21 point‐of‐care ultrasound and educational leaders representing 15 of 17 (88%) Canadian medical schools was formed and participated in a modified Delphi consensus method. Experts anonymously rated 195 curricular elements on their appropriateness to include in a medical school curriculum using a 5‐point Likert scale. The group defined consensus as 70% or more experts agreeing to include or exclude an element. We determined a priori that no more than 3 rounds of voting would be performed. Results: Of the 195 curricular elements considered in the first round of voting, the group reached consensus to include 78 and exclude 24. In the second round, consensus was reached to include 4 and exclude 63 elements. In our final round, with 1 additional item added to the survey, the group reached consensus to include an additional 3 and exclude 8 elements. A total of 85 curricular elements reached consensus to be included, with 95 to be excluded. Sixteen elements did not reach consensus to be included or excluded. Conclusions: By expert opinion‐based consensus, the Canadian Ultrasound Consensus for Undergraduate Medical Education Group recommends that 85 curricular elements be considered for inclusion for teaching in the Canadian medical school focused ultrasound curricula.